Using the 4-D to Design a Public Speaking Handbook for Students at Miftahul Ulum Boarding School - Imroatul Fathonah; Andi Tenrisanna Syam; Amalia Yahya (Schemata: Jurnal Pascasarjana UIN Mataram, 2025)
This study was conducted to design a Public Speaking Handbook for students enrolled at the Miftahul Ulum Islamic school Boarding. The authors employed the R&D (Research and Development) method by adopting the 4-D model. The research instruments were observation, interviews, and surveys. The research participants comprised 29 students, one teacher, and several other lecturers, who were selected using a purposive sampling method. Quantitative data was collected from surveys, while qualitative data was collected from student records and observations. The researchers conducted a needs analysis and a perception survey on the manual among students. The students' perception score was 3.41, which was considered "good." Twenty-nine respondents participated in the pilot study. The experts’ verification and students’ perception results meet the content, design, and format criteria and constitute attractive educational material that reflects students' needs, preferences, and deficiencies. This demonstrates that its development is feasible.